Tables of verbal derivatives in -š- in the Saami languages ... - Kuokkala, Juha; Koponen, Eino (Zenodo, 2023)
The tables present the occurrence of verbs with a suffixal -š- (-šš-) by tabulating the attested derivatives across the Saami languages. Base words are given in their North Saami form by default, including approximate meanings in Finnish or the language used in sources in question. The corresponding entry number of Eliel Lagercranz's Lappischer Wortschatz (1939) is also given when applicable. For more information about sources etc., see the paper to which this is an appendix: Kuokkala, Juha & Koponen, Eino. 2023. On the distribution and history of Saami verbal derivatives in -š- . Journal of Estonian and Finno-Ugric Linguistics 14(3). 73–105. https://doi.org/10.12697/jeful.2023.14.3.03 ...